Mathematical macromodeling of infilled frames: State of the art - Asteris, Panagiotis G.; Antoniou, S.T.; Sophianopoulos, Dimitris S.; Chrysostomou, Christis (My University, 2011)
The primary objective of this paper is to present a general review of the different macromodels used for the analysis of infilled frames. A number of distinct approaches in the field of analysis of infilled frames since the mid-1950s have yielded several analytical models. These studies stressed that the numerical simulation of infilled frames is difficult and generally unreliable because of the very large number of parameters to be taken into account and the magnitude of the uncertainties associated with most of them. In this paper, the advantages and disadvantages of each macromodel are pointed out, and practical recommendations for the implementation of the different models are indicated.
Keywords: Failure modes; Infilled frames; Macromodels; Masonry